En amerikansk disputats om Grundtvigs hermeneutik. Donald Juel Sneen: The Hermeneutics of N.F.S. Grundtvig, dissertation fra Princeton Theological Seminary 1968 - Simonsen, Hejne (Grundtvig-studier, 1984)
The Hermeneutics of N . F. S. Grundtvig, by Donald Juel Sneen. A dissertation from Princeton Theological Seminary 1968 (University Microfilms, Ann Arbor, Michigan) XVII + 336 pages.Reviewed by Professor Hejne Simonsen, D.D. Aarhus University There is no monography available to cover this subject in its entirety. And with regard to Grundtvig’s manuscripts Sneen has been entirely dependent on the publications of others. He also builds on the existing standard editions as well as on a number of Grundtvig’s published sermons: the Biblical Sermons, The Sunday Book, Sermons in Frederik’s Church, Vartov Sermons and Last Sermons.Grundtvig’s poetry gives way to his prose. The book has the character of an introduction. One might have expected more discussion of Grundtvig research, in particular Kaj Thaning’s Man First - , which was published five years before this work. Sneen is very much dependent on Hal Koch’s book on Grundtvig, which is contrasted with “the psychoanalytic trend of earlier studies by H. Helwig and J. P. Bang” .The main chapters are: Hermeneutics as Understanding: Historical and Existential, and Hermeneutics as Interpretation of the Biblical Context, (chaps. 2 & 3). According to Sneen Grundtvig’s view of history is fundamental to his hermeneutic principles in general. But the contrary terms life-death and speaking- writing are also explained. Light is shed on a number of basic concepts such as “ Childlike Faith” , “the Heart” , and “the Mother-Tongue” . But chapter 2 is difficult to survey. In contrast chapter 3 is clear and simple in its construction.The creed is used as the hermeneutic key to an interpretation of the biblical message. Sneen here succeeds in drawing a fair picture of Grundtvig’s understanding of the basic content of the faith. The last two chapters – School and Scripture, and Church and Scripture - deal with Grundtvig’s exegesis. The author’s conclusions are largely positive, but it is maintained that Grundtvig’s attitude to historical-critical methods was pre-critical, and Sneen regrets Grundtvig’s lack of distinction between the oral tradition and the kerygma. His view has thus not found as much relevance for the present-day as it might have done.According to Hejne Simonsen, Sneen’s negative evaluation of Grundtvig’s knowledge of New Testament textual criticism might have been modified if Sneen had known of Grundtvig’s essay On the New Testament in its Original Language (Scandinavian Church Times 1837). This essay also affords grounds to question the evaluation of Grundtvig’s relationship to the historical method as pre-critical. For Sneen refers merely to a brief article by Grundtvig on D. F. Strauss, The Life of Jesus (Das Leben Jesu), printed in Begtrup’s edition (vol. VIII).Sneen maintains (p. 256) that in general allegorical interpretation is a rarity in Grundtvig: but Hejne Simonsen begs to differ when one looks at his sermons. And in The Pleiades (Seven Stars) of Christendom, which is given detailed treatment, we find a peculiarly typological exegesis. Here mention should have been made of the fact that in his introduction Grundtvig points out that in criticism of the poem’s interpretation of the Revelation of St John (as a prophecy in the history of the Church) a distinction must be made between the two questions, “one, to what extent is the general view apposite, useful and joyful for Christians? and two, to what extent is this general view predicted and prepared by the Apostle John, so that the second could well be very doubtful and yet the first just right.” Grundtvig believes that the letters to the churches in the apocalypse have a message for the churches which the apostolic author was not aware of when they were written (cf. already in 1812 Grundtvig writes that “it is the true mark of a prophecy that it is enigmatic writing until the passage of time illuminates it.” (Biblical Sermons, 1883, p. 345). In Last Sermons vol. II p. 234, where Grundtvig is discussing one side of his view of Revelation he adds “that all this kind of thing in no way belongs to the Childhood Christian Teachings or to a common Creed for salvation, but only to the gradual enlightenment of God’s counsel and mysterious deeds...” Here the Creed takes on a critical function, so that he can distinguish between what every Christian must believe and confess, and what belongs to the free enlightenment of God’s salvation purpose, which must be illuminated little by little. It is here that the liberating effect of his own “enlightenment” in 1825 becomes apparent.In spite of the errors and inaccuracies in the work it is of interest both in its choice of subject and in the path it has cut for itself through the wilderness, for this is an otherwise neglected subject.